Supported charcoal-based composite catalyst MnFe-LDH-coated Co-CC and preparation method and application thereof

By using molten salt hydrate pretreatment and sonication technology to prepare the supported biochar-based composite catalyst MnFe-LDH@Co-CC under low temperature conditions, the problem of high cost of traditional pyrolysis processes and difficult catalysts to degrade coexisting antibiotics is solved, and the problem of high cost of traditional pyrolysis processes is solved, thus achieving the goal of achieving the problem of coexisting antibiotics with high cost and difficulty in degrading the catalyst. It has efficient and environmentally friendly water purification effect.

CN119259070APending Publication Date: 2025-01-07BEIHUA UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411391369.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When dealing with antibiotic pollution in complex water environments, the catalyst preparation conditions are harsh, the reaction energy consumption is high, and it is difficult to degrade coexisting antibiotics. The traditional pyrolysis carbonization process is costly, making it difficult to meet the economic benefits requirements of large-scale production.

Method used

Biochar was prepared under low temperature conditions by using molten salt hydrate pretreatment technology, and the supported biochar-based composite catalyst MnFe-LDH@Co-CC was constructed through ultrasonic treatment and water bath reaction, combining ferromanganese salt and cobalt modification for activation. Potassium bisulfate degrades coexisting antibiotics in water.

Benefits of technology

It realizes efficient removal of coexisting antibiotics in water under low temperature conditions, the catalyst can be reused, reduces energy consumption and cost, and is non-toxic and pollution-free, suitable for green and environmentally friendly water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259070A_ABST
    Figure CN119259070A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biochar-based catalysts, and provides a supported biochar-based composite catalyst MnFe-LDH-coated Co-CC as well as a preparation method and application of the supported biochar-based composite catalyst MnFe-LDH-coated Co-CC. The method comprises the following steps: mixing straw powder and an acidic LiBr molten salt hydrate, and carrying out a reaction to obtain biochar; mixing the biochar with a cobalt chloride solution, and dropwise adding a sodium borohydride solution into the mixed solution to obtain cobalt-loaded biochar; mixing the cobalt-loaded biochar with a ferromanganese salt solution to obtain a mixed solution, dropwise adding an alkaline solution into the mixed solution to obtain a turbid liquid, and sequentially carrying out ultrasonic treatment and water bath reaction on the turbid liquid to obtain the loaded biochar-based composite catalyst. The composite catalyst is a non-toxic, pollution-free, green and environment-friendly catalyst, can quickly and efficiently degrade coexisting antibiotics in water, is used as a heterogeneous reaction catalyst, is easy to separate from a reaction system and can be repeatedly used, and the use cost of the catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biochar-based catalysts, and in particular to a supported biochar-based composite catalyst MnFe-LDH@Co-CC and a preparation method and application thereof. Background Art

[0002] In recent years, the rapid development of industry, agriculture and emerging industries has brought many problems, especially the threat to the water environment. The water environment is complex, and bacterial resistance caused by antibiotic pollution in the environment has become a major challenge threatening human health. Therefore, it is necessary to develop a long-term, stable and efficient catalytic system to deal with antibiotic pollution in complex water environments.

[0003] At present, peroxymonosulfate (PMS)-based advanced oxidation processes are widely used in the field of water treatment. Due to its advantages of economy, high efficiency, environmental protection, safety and stability, peroxymonosulfate-based advanced oxidation processes have great prospects for removing antibiotics. PMS has a long OO bond and an asymmetric structure, and can be activated by a variety of methods to produce free radicals, such as electroactivation, thermal activation, ultraviolet light activation and catalyst activation. Among them, the heterogeneous catalytic degradation method constructed by adding a catalyst is easy to recover and can be reused, which is considered to be a feasible PMS activation method.

[0004] Carbon materials are widely used in environmental remediation and catalyst preparation due to their large specific surface area and rich surface groups. Biomass is an ideal raw material for synthesizing carbon materials because of its abundant resources, renewability, and environmental friendliness. Biomass carbonization methods include pyrolysis, hydrothermal carbonization, and flash carbonization of carbon precursors in an inert atmosphere. At present, pyrolysis is the mainstream process for producing biochar. The reaction temperature of pyrolysis carbonization is 400-800℃, which has strict requirements on the reactor and high energy consumption. The high cost exceeds the expected economic benefits of large-scale production of biochar. Therefore, it is particularly urgent to explore an innovative technology that effectively reduces the reaction temperature to improve economic efficiency while maintaining the inherent properties of biochar. Molten salt hydrate pretreatment technology provides a solution to this challenge. It can reduce the crystallinity of cellulose, change the specific surface area and pore structure of biomass raw materials, and thus overcome the limitations of traditional pyrolysis methods.

[0005] Usually, biochar is modified and modified after it is obtained to improve its activation ability. Transition metals are one of the common modification materials. However, metal modification can easily cause the concentration of metal ions in the solution to exceed the standard. The introduction of layered double hydroxides (LDH) with high adsorption capacity can effectively reduce the leaching of metal ions. Layered double hydroxides are composed of two or more metal elements and interlayer anions. They are a structurally adjustable two-dimensional material. The special layered structure and large surface area make them potential adsorbents and PMS activators in the field of water treatment. Although these catalysts can activate PMS to degrade antibiotics in water in a short time, they still have the disadvantages of harsh preparation conditions, high reaction energy consumption, and potential environmental pollution risks, and most of them are targeted at the degradation of a single antibiotic. The situation in the real water environment is complicated, and multiple antibiotics with different structures often coexist. However, it is difficult to separate and purify a single antibiotic in the water treatment process, and the catalytic system that only works on a single antibiotic cannot meet the purification needs of complex water environments.

[0006] Therefore, it is of great significance to realize the carbonization process of biomass under low-temperature conditions and construct a catalytic system that combines the advantages of biochar, metals and layered double hydroxides for the degradation of coexisting antibiotics in water bodies. Summary of the invention

[0007] The purpose of the present invention is to provide a supported biochar-based composite catalyst MnFe-LDH@Co-CC and a preparation method and application thereof in order to overcome the deficiencies of the prior art.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a supported biochar-based composite catalyst MnFe-LDH@Co-CC, comprising the following steps:

[0010] 1) mixing straw powder and acidic LiBr molten salt hydrate and reacting them to obtain biochar;

[0011] 2) mixing the biochar and the cobalt chloride solution, and adding a sodium borohydride solution dropwise into the mixture to obtain the cobalt-loaded biochar;

[0012] 3) The cobalt-loaded biochar and the manganese iron salt solution are mixed to obtain a mixed solution, an alkaline solution is added dropwise to the mixed solution to obtain a suspension, and the suspension is subjected to ultrasonic treatment and water bath reaction in sequence to obtain a loaded biochar-based composite catalyst MnFe-LDH@Co-CC.

[0013] Preferably, in step 1), the mass ratio of the straw powder to the acidic LiBr molten salt hydrate is 1:18-22; the acidic LiBr molten salt hydrate is a mixture of LiBr and hydrochloric acid, in which the mass fraction of LiBr is 30-60% and the concentration of hydrochloric acid is 0.4-0.6 mol / L.

[0014] Preferably, the reaction temperature in step 1) is 140-240° C., the reaction time is 140-160 min; and the mixing time is 1.5-2.5 h.

[0015] Preferably, in step 2), the concentration of the cobalt chloride solution is 0.015-0.025 mol / L, and the concentration of the sodium borohydride solution is 0.025-0.035 mol / L; the mass volume ratio of the biochar to the cobalt chloride solution is 0.09-0.11 g:9-11 mL, and the volume ratio of the cobalt chloride solution to the sodium borohydride solution is 9-11:9-11.

[0016] Preferably, the manganese iron salt solution in step 3) is a mixture of manganese acetate and ferric nitrate, in which the concentrations of manganese acetate and ferric nitrate are independently 0.009-0.011 mol / L, and the alkaline solution is a mixture of sodium hydroxide and sodium carbonate, in which the concentration of sodium hydroxide is 0.3-0.4 mol / L, and the concentration of sodium carbonate is 0.12-0.18 mol / L.

[0017] Preferably, in step 3), the mass volume ratio of the cobalt-loaded biochar to the ferromanganese salt solution is 0.09-0.11 g: 45-55 mL; the volume ratio of the ferromanganese salt solution to the alkaline solution is 45-55: 45-55;

[0018] After the alkaline solution was added dropwise, the pH value of the suspension was adjusted to 10.4-10.7.

[0019] Preferably, in step 3), the reagent for adjusting the pH value of the suspension is hydrochloric acid, and the concentration of the hydrochloric acid is 2.5-3.5 mol / L; the mixing time is 28-32 min; the ultrasonic treatment time is 28-32 min; the water bath reaction temperature is 60-70°C, and the water bath reaction time is 3-5 h.

[0020] The present invention also provides a supported biochar-based composite catalyst MnFe-LDH@Co-CC prepared by the preparation method.

[0021] The present invention also provides the use of the supported biochar-based composite catalyst MnFe-LDH@Co-CC in activating potassium persulfate to degrade antibiotics.

[0022] Preferably, the supported biochar-based composite catalyst MnFe-LDH@Co-CC, the mixed antibiotic solution and potassium persulfate are mixed, and the mixed solution is reacted; the reaction time is 35 to 45 minutes;

[0023] In the mixed solution, the concentration of the loaded biochar-based composite catalyst MnFe-LDH@Co-CC is 0.05-0.30 g / L, and the concentration of potassium persulfate is 3.0-4.5 mmol / L; the antibiotics include amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin, and the concentrations of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin are independently 95-105 mg / L.

[0024] The beneficial effects of the present invention include the following:

[0025] 1) The present invention uses acidic LiBr molten salt hydrate to treat corn stalks to prepare biochar under low temperature conditions, and the biochar is modified to prepare the catalyst MnFe-LDH@Co-CC, which is used to degrade high concentrations of coexisting antibiotics (including amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin) in water. The supported biochar-based composite catalyst of the present invention achieves efficient removal of coexisting antibiotics, and the catalytic performance does not show a significant decrease after five cycles of use.

[0026] 2) The loaded biochar-based composite catalyst MnFe-LDH@Co-CC prepared by the present invention is a non-toxic, pollution-free, green and environmentally friendly catalyst that can quickly and efficiently degrade coexisting antibiotics in water. As a heterogeneous reaction catalyst, it is easy to separate from the reaction system and can be reused, thereby reducing the cost of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 These are SEM images of the supported biochar-based composite catalyst MnFe-LDH@Co-CC of Example 1 at different magnifications. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a supported biochar-based composite catalyst MnFe-LDH@Co-CC, comprising the following steps:

[0029] 1) mixing straw powder and acidic LiBr molten salt hydrate and reacting them to obtain biochar;

[0030] 2) mixing the biochar and the cobalt chloride solution, and adding a sodium borohydride solution dropwise into the mixture to obtain the cobalt-loaded biochar;

[0031] 3) The cobalt-loaded biochar and the manganese iron salt solution are mixed to obtain a mixed solution, an alkaline solution is added dropwise to the mixed solution to obtain a suspension, and the suspension is subjected to ultrasonic treatment and water bath reaction in sequence to obtain a loaded biochar-based composite catalyst MnFe-LDH@Co-CC.

[0032] In the present invention, the mass ratio of the straw powder and the acidic LiBr molten salt hydrate in step 1) is preferably 1:18-22, more preferably 1:19-21, and more preferably 1:20; the acidic LiBr molten salt hydrate is a mixture of LiBr and hydrochloric acid, in which the mass fraction of LiBr is preferably 30-60%, more preferably 40-50%, and more preferably 45%; the concentration of hydrochloric acid is preferably 0.4-0.6 mol / L, more preferably 0.45-0.55 mol / L, and more preferably 0.5 mol / L.

[0033] In the present invention, the reaction temperature in step 1) is preferably 140-240°C, more preferably 160-220°C, and more preferably 170-200°C; the reaction time is preferably 140-160 min, more preferably 145-155 min, and more preferably 150 min; the mixing time is preferably 1.5-2.5 h, and more preferably 2 h.

[0034] In the present invention, the straw powder is preferably corn straw powder.

[0035] In the present invention, the concentration of the cobalt chloride solution in step 2) is preferably 0.015-0.025 mol / L, more preferably 0.018-0.022 mol / L, and more preferably 0.02 mol / L; the concentration of the sodium borohydride solution is preferably 0.025-0.035 mol / L, more preferably 0.028-0.032 mol / L, and more preferably 0.03 mol / L; the mass volume ratio of biochar and cobalt chloride solution is preferably 0.09-0.11 g:9-11 mL, and more preferably 0.1 g:10 mL, and the volume ratio of cobalt chloride solution to sodium borohydride solution is preferably 9-11:9-11, and more preferably 10:10.

[0036] In the present invention, the mixing time in step 2) is preferably 28 to 32 minutes, more preferably 30 minutes; and the mixed solution is preferably stirred during the dropwise addition of the sodium borohydride solution until there are no bubbles in the system.

[0037] In the present invention, the manganese iron salt solution in step 3) is preferably a mixture of manganese acetate and ferric nitrate, and the concentrations of manganese acetate and ferric nitrate in the manganese iron salt solution are independently preferably 0.009-0.011 mol / L, and more preferably 0.01 mol / L; the alkaline solution is preferably a mixture of sodium hydroxide and sodium carbonate, and in the alkaline solution, the concentration of sodium hydroxide is preferably 0.3-0.4 mol / L, and more preferably 0.32-0.38 mol / L, and more preferably 0.35-0.36 mol / L, and the concentration of sodium carbonate is preferably 0.12-0.18 mol / L, and more preferably 0.14-0.15 mol / L.

[0038] In the present invention, the mass volume ratio of the cobalt-loaded biochar and the ferromanganese salt solution in step 3) is preferably 0.09-0.11 g: 45-55 mL, more preferably 0.1 g: 48-52 mL, and more preferably 0.1 g: 50 mL; the volume ratio of the ferromanganese salt solution to the alkaline solution is preferably 45-55: 45-55, more preferably 48-52: 48-52, and more preferably 50: 50;

[0039] After the alkaline solution is added dropwise, the pH value of the suspension is adjusted. The pH value of the suspension is preferably adjusted to 10.4 to 10.7, and more preferably 10.5 to 10.6.

[0040] In step 3) of the present invention, the reagent for adjusting the pH value of the suspension is preferably hydrochloric acid, and the concentration of hydrochloric acid is preferably 2.5-3.5 mol / L, more preferably 2.8-3.2 mol / L, and more preferably 3 mol / L; the mixing time is preferably 28-32 min, and more preferably 30 min; the ultrasonic treatment time is preferably 28-32 min, and more preferably 30 min; the water bath reaction temperature is preferably 60-70 ° C, and more preferably 62-68 ° C, and more preferably 65-66 ° C; the water bath reaction time is preferably 3-5 h, and more preferably 3.5-4.5 h, and more preferably 4 h.

[0041] In the present invention, the mixture obtained by the reaction in step 1) is filtered, and the separated solids are washed and dried in sequence to obtain biochar; in step 2) the system after the sodium borohydride solution is added dropwise is filtered, and the separated solids are washed and dried in sequence to obtain cobalt-loaded biochar; in step 3) the product after the water bath reaction is filtered, and the separated solids are washed and dried in sequence to obtain a loaded biochar-based composite catalyst MnFe-LDH@Co-CC; the reagents used for washing in steps 1) to 3) are water and anhydrous ethanol in sequence, and the number of washings with water and anhydrous ethanol is independently preferably 2 to 4 times, and more preferably 3 times; the drying temperature is independently preferably 55 to 65°C, more preferably 58 to 62°C, and more preferably 60°C; the drying time is independently preferably 10 to 14h, more preferably 11 to 13h, and more preferably 12h.

[0042] The present invention also provides a supported biochar-based composite catalyst MnFe-LDH@Co-CC prepared by the preparation method.

[0043] The present invention also provides the use of the supported biochar-based composite catalyst MnFe-LDH@Co-CC in activating potassium persulfate to degrade antibiotics.

[0044] In the present invention, the supported biochar-based composite catalyst MnFe-LDH@Co-CC, the mixed antibiotic solution and potassium persulfate are mixed, and the mixed solution is reacted; the reaction time is preferably 35 to 45 minutes, more preferably 37 to 43 minutes, and more preferably 39 to 40 minutes;

[0045] In the mixed solution, the concentration of the supported biochar-based composite catalyst MnFe-LDH@Co-CC is preferably 0.05-0.30 g / L, more preferably 0.10-0.25 g / L, and more preferably 0.15-0.20 g / L. The concentration of potassium persulfate is preferably 3.0-4.5 mmol / L, and more preferably 3.5-4.0 mmol / L. The antibiotics include amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin. The concentrations of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin are independently preferably 95-105 mg / L, more preferably 97-103 mg / L, and more preferably 100 mg / L.

[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0047] Example 1

[0048] Corn straw powder (300 mesh) with a mass ratio of 1:20 and acidic LiBr molten salt hydrate (acidic LiBr molten salt hydrate is a mixture of LiBr and hydrochloric acid, the mass fraction of LiBr is 50%, and the concentration of hydrochloric acid is 0.5 mol / L) are mixed in a pressure vessel, stirred at 500 rpm for 2 hours at room temperature, and then transferred to an oven and reacted at 170°C for 150 minutes. The reaction mixture is filtered for solid-liquid separation, and the separated solid is washed with deionized water 3 times and then washed with anhydrous ethanol 3 times, and then dried at 60°C for 12 hours to obtain biochar.

[0049] 0.1g biochar was ultrasonically mixed with 10mL 0.02mol / L CoCl2 solution at 300W for 30min, and 10mL 0.03mol / L NaBH4 solution was added dropwise at a rate of 0.1mL / s at room temperature and a stirring rate of 500rpm, and stirred until there were no bubbles. The system after the reaction was filtered for solid-liquid separation, and the separated solid was washed 3 times with deionized water and 3 times with anhydrous ethanol, and then dried at 60℃ for 12h to obtain biochar loaded with cobalt.

[0050] 0.1g of biochar loaded with cobalt was added to 50mL of manganese iron salt solution (the concentration of manganese acetate and ferric nitrate was 0.01mol / L) and stirred for 30min, and then 50mL of alkaline solution (the concentration of sodium hydroxide was 0.35mol / L and the concentration of sodium carbonate was 0.15mol / L) was added at a rate of 0.1mL / s to obtain a suspension. The pH value of the suspension was adjusted to 10.5 with 3mol / L hydrochloric acid, and then the suspension was ultrasonically treated at a power of 300W for 30min and placed in a water bath at 65℃ and stirred at a rate of 500rpm for 4h. The product after the water bath reaction was separated by filtration, and the solid was washed with deionized water 3 times and then washed with anhydrous ethanol 3 times, and then dried at 60℃ for 12h to obtain the loaded biochar-based composite catalyst MnFe-LDH@Co-CC.

[0051] The SEM images of the supported biochar-based composite catalyst MnFe-LDH@Co-CC of Example 1 at different magnifications are shown in FIG. Figure 1 shown.

[0052] Example 2

[0053] Corn straw powder (300 mesh) with a mass ratio of 1:19 and acidic LiBr molten salt hydrate (acidic LiBr molten salt hydrate is a mixture of LiBr and hydrochloric acid, the mass fraction of LiBr is 40%, and the concentration of hydrochloric acid is 0.45 mol / L) are mixed in a pressure vessel, stirred at a rate of 500 rpm for 1.5 hours at room temperature, and then transferred to an oven and reacted at 160°C for 160 minutes. The reaction mixture is filtered for solid-liquid separation, and the separated solid is washed with deionized water 3 times and then washed with anhydrous ethanol 3 times, and then dried at 55°C for 13 hours to obtain biochar.

[0054] 0.1g biochar was ultrasonically mixed with 9mL 0.018mol / L CoCl2 solution at 300W for 28min, and 9mL 0.028mol / L NaBH4 solution was added dropwise at a rate of 0.1mL / s at room temperature and a stirring rate of 500rpm, and stirred until there were no bubbles. The system after the reaction was filtered for solid-liquid separation, and the separated solid was washed 3 times with deionized water and 3 times with anhydrous ethanol, and then dried at 55°C for 13h to obtain cobalt-loaded biochar.

[0055] 0.1g of biochar loaded with cobalt was added to 48mL of manganese iron salt solution (the concentration of manganese acetate and ferric nitrate was 0.009mol / L) and stirred for 28min, and then 48mL of alkaline solution (the concentration of sodium hydroxide was 0.32mol / L and the concentration of sodium carbonate was 0.12mol / L) was added at a rate of 0.1mL / s to obtain a suspension. The pH value of the suspension was adjusted to 10.4 with 2.8mol / L hydrochloric acid, and then the suspension was ultrasonically treated at a power of 300W for 28min and placed in a water bath at 62℃ and stirred at a rate of 500rpm for 4.5h. The product after the water bath reaction was separated by filtration, and the solid was washed with deionized water 3 times and then washed with anhydrous ethanol 3 times, and then dried at 55℃ for 13h to obtain the loaded biochar-based composite catalyst MnFe-LDH@Co-CC.

[0056] Example 3

[0057] Corn straw powder (300 mesh) with a mass ratio of 1:21 and acidic LiBr molten salt hydrate (acidic LiBr molten salt hydrate is a mixture of LiBr and hydrochloric acid, the mass fraction of LiBr is 45%, and the concentration of hydrochloric acid is 0.55 mol / L) are mixed in a pressure vessel, stirred at a rate of 500 rpm for 2.5 hours at room temperature, and then transferred to an oven and reacted at 200°C for 140 minutes. The reaction mixture is filtered for solid-liquid separation, and the separated solid is washed with deionized water 3 times and then washed with anhydrous ethanol 3 times, and then dried at 65°C for 11 hours to obtain biochar.

[0058] 0.1g biochar was ultrasonically mixed with 11mL 0.022mol / L CoCl2 solution at 300W for 32min, and 11mL 0.032mol / L NaBH4 solution was added dropwise at a rate of 0.1mL / s at room temperature and a stirring rate of 500rpm, and stirred until there were no bubbles. The system after the reaction was filtered for solid-liquid separation, and the separated solid was washed 3 times with deionized water and 3 times with anhydrous ethanol, and then dried at 65℃ for 11h to obtain biochar loaded with cobalt.

[0059] 0.1g of biochar loaded with cobalt was added to 52mL of manganese iron salt solution (the concentration of manganese acetate and ferric nitrate was 0.011mol / L) and stirred for 32min, and then 52mL of alkaline solution (the concentration of sodium hydroxide was 0.38mol / L and the concentration of sodium carbonate was 0.18mol / L) was added at a rate of 0.1mL / s to obtain a suspension. The pH value of the suspension was adjusted to 10.6 with 3.2mol / L hydrochloric acid, and then the suspension was ultrasonically treated at a power of 300W for 32min and placed in a water bath at 68℃ and stirred at a rate of 500rpm for 3.5h. The product after the water bath reaction was separated by filtration, and the solid was washed with deionized water 3 times and then washed with anhydrous ethanol 3 times, and then dried at 65℃ for 11h to obtain the loaded biochar-based composite catalyst MnFe-LDH@Co-CC.

[0060] The supported biochar-based composite catalyst MnFe-LDH@Co-CC of Examples 1 to 3 was used to activate potassium persulfate to degrade antibiotics: 0.20 g / L of the supported biochar-based composite catalyst MnFe-LDH@Co-CC of Examples 1 to 3 was added to 100 mL of a mixed antibiotic solution (in the mixed antibiotic solution, 10 mg each of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin), 4.0 mmol / L of potassium persulfate was added, and after reacting for 40 minutes, the concentration of each antibiotic after the reaction was detected by high performance liquid chromatography (HPLC). The removal rates of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin by MnFe-LDH@Co-CC in Example 1 are 100%, 100%, 99.2% and 94.9% respectively; the removal rates of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin by MnFe-LDH@Co-CC in Example 2 are 100%, 100%, 99.1% and 94.7% respectively; the removal rates of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin by MnFe-LDH@Co-CC in Example 3 are 100%, 100%, 99.4% and 95.0% respectively. After five cycles of use, the removal rates of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin by the composite catalyst MnFe-LDH@Co-CC in Examples 1 to 3 did not show a significant decrease.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a supported biochar-based composite catalyst MnFe-LDH@Co-CC, characterized in that: The following steps are included: 1) mixing straw powder and acidic LiBr molten salt hydrate and reacting them to obtain biochar; 2) mixing the biochar and the cobalt chloride solution, and adding a sodium borohydride solution dropwise into the mixture to obtain the cobalt-loaded biochar; 3) The cobalt-loaded biochar and the manganese iron salt solution are mixed to obtain a mixed solution, an alkaline solution is added dropwise to the mixed solution to obtain a suspension, and the suspension is subjected to ultrasonic treatment and water bath reaction in sequence to obtain a loaded biochar-based composite catalyst MnFe-LDH@Co-CC.

2. The preparation method according to claim 1, characterized in that: Step 1) The mass ratio of the straw powder to the acidic LiBr molten salt hydrate is 1:18-22; the acidic LiBr molten salt hydrate is a mixture of LiBr and hydrochloric acid, in which the mass fraction of LiBr is 30-60% and the concentration of hydrochloric acid is 0.4-0.6 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that: Step 1) The reaction temperature is 140-240° C., the reaction time is 140-160 min; the mixing time is 1.5-2.5 h.

4. The preparation method according to claim 3, characterized in that: Step 2) The concentration of the cobalt chloride solution is 0.015-0.025 mol / L, and the concentration of the sodium borohydride solution is 0.025-0.035 mol / L; the mass volume ratio of the biochar to the cobalt chloride solution is 0.09-0.11 g:9-11 mL, and the volume ratio of the cobalt chloride solution to the sodium borohydride solution is 9-11:9-11.

5. The preparation method according to claim 1 or 4, characterized in that: Step 3) The manganese iron salt solution is a mixture of manganese acetate and ferric nitrate, in which the concentrations of manganese acetate and ferric nitrate are independently 0.009-0.011 mol / L, and the alkaline solution is a mixture of sodium hydroxide and sodium carbonate, in which the concentration of sodium hydroxide is 0.3-0.4 mol / L, and the concentration of sodium carbonate is 0.12-0.18 mol / L.

6. The preparation method according to claim 5, characterized in that: Step 3) The mass volume ratio of the cobalt-loaded biochar to the ferromanganese salt solution is 0.09-0.11 g: 45-55 mL; the volume ratio of the ferromanganese salt solution to the alkaline solution is 45-55: 45-55; After the alkaline solution was added dropwise, the pH value of the suspension was adjusted to 10.4-10.

7.

7. The preparation method according to claim 5, characterized in that: In step 3), the reagent for adjusting the pH value of the suspension is hydrochloric acid, and the concentration of hydrochloric acid is 2.5-3.5 mol / L; the mixing time is 28-32 min; the ultrasonic treatment time is 28-32 min; the water bath reaction temperature is 60-70° C., and the water bath reaction time is 3-5 h.

8. The supported biochar-based composite catalyst MnFe-LDH@Co-CC prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the supported biochar-based composite catalyst MnFe-LDH@Co-CC according to claim 8 in activating potassium persulfate to degrade antibiotics.

10. The use according to claim 9, characterized in that: The supported biochar-based composite catalyst MnFe-LDH@Co-CC, the mixed antibiotic solution and potassium persulfate are mixed, and the mixed solution is reacted; the reaction time is 35 to 45 minutes; In the mixed solution, the concentration of the loaded biochar-based composite catalyst MnFe-LDH@Co-CC is 0.05-0.30 g / L, and the concentration of potassium persulfate is 3.0-4.5 mmol / L; the antibiotics include amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin, and the concentrations of amoxicillin, tetracycline hydrochloride, sulfamethoxazole and norfloxacin are independently 95-105 mg / L.